Students’ learning styles and their academic performance in Accounting Course / Wan Mardyatul Miza Wan Tahir... [et al.] - Wan Tahir, Wan Mardyatul Miza; Dol @ Abdul Wahid, Akma Hidayu; Hussin, Amariah Hanum; Abdul Jabar, Ja’izah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Learning accounting for non-accounting major students is constantly considered challenging. Therefore, the objective of the study is to identify the relationship between the learning style adopted by non-accounting students in learning accounting course and the impact on their course performance. The Kolb’s learning style survey model that wasredesigned by Honey and Mumford in 1986 was adopted to recognise the learning style preferred by students. The students’ academic performance in accounting course was obtained from their scores in major assessment methods including assignment, test, quiz,and final examination result, which represented their final grade. Further, this paper identified other factors affecting students’ academic performance. The result indicated that students who adopted the Pragmatist and Theorist learning styles were more excellent in their academic performance in accounting course, while those who adopted the Activist learning style were poorer in their academic result. Accordingly, accounting course does not only involve number, data, and calculation but requires fact-finding and applying critical thinking, areas in which the Activist learning style lacks. Other factors found that educators who conducted the lecture were recognised as important contributors towards the students’ achievement in accounting course. Nevertheless,students with a higher level of anxiety performed better academically as compared to those with low anxiety. In conclusion, to succeed in accounting course, students should not rely merely on one style in the learning process.